A CRITICAL REVIEW: STUDENTS OUTCOMES OF PROJECT BASED LEARNING (PJBL ) - Sa'adah, Halimatus; Wahyuni, Sri (Universitas Muria Kudus, 2024)
The purpose of study is to investigate the impact and effectiveness of implementing Project Based Learning (PjBL) towards learning outcomes in English Subject. The PjBL method has become a major focus in education due to its potential to increase student’s involvement and practical in learning. The method of this research used a Systematic Literature Review. The selection of the inclusion and exclusion criteria has been determined. It were selected 28 included studies obtained from three databases, Connectedpapers.com, ERIC, Perplexity.ai. This study analyzes the characteristics studies, impact and effectiveness of Project Based Learning (PjBL) on learning outcomes in English language subjects. Based on the results of this study, it is emphasized that PjBL has positive and significant implications. It is shown that PjBL can have a beneficial impact on students' ability to learn and use English. Through contextualized and practical projects, students don not only practice but they are also actively involved in learning process. the impact of their involvement, it does not only improves specific language skills, but also strengthens their social skills, collaboration skills and motivation to learn. Therefore, it can be concluded that learning focused on the application of PjBL in the context of English can support learning outcomes optimally.